Antimicrobial resistance patterns in bacteria causing febrile illness in Africa, South Asia, and Southeast Asia: a systematic review of published etiological studies from 1980-2015. (September 2022) - Roberts, Tamalee; Dahal, Prabin; Shrestha, Poojan; Schilling, William; Shrestha, Rujan; Ngu, Roland; Huong, Vu Thi Lan; van Doorn, H Rogier; Phimolsarnnousith, Vilayouth; Miliya, Thyl; Crump, John A; Bell, David; et al.
Highlights: A total of 371 articles over 35 years included the target pathogen-drug combinations. There is an increase in antimicrobial resistance reporting in Africa and Asia. Pooled proportions of resistance are high for third-generation cephalosporins. Quinolone resistance in Salmonella enterica is increasing in Asia. There is a lack of standardization in microbiology laboratory testing and reporting. Abstract: Objective: In this study, we aimed to conduct a systematic review to characterize antimicrobial resistance (AMR) patterns for bacterial causes of febrile illness in Africa and Asia. Methods: We included published literature from 1980-2015 based on data extracted from two recent systematic reviews of nonmalarial febrile illness from Africa, South Asia, and Southeast Asia. Selection criteria included articles with full bacterial identification and antimicrobial susceptibility testing (AST) results for key normally sterile site pathogen-drug combinations. Pooled proportions of resistant isolates were combined using random effects meta-analysis. Study data quality was graded using the Microbiology Investigation Criteria for Reporting Objectively (MICRO) framework. Results: Of 3475 unique articles included in the previous reviews, 371 included the target pathogen-drug combinations. Salmonella enterica tested against ceftriaxone and ciprofloxacin were the two highest reported combinations (30, 509 and 22, 056 isolates, respectively). Pooled proportions of resistant isolates were high for third-generation cephalosporins for Klebsiella pneumoniae and Escherichia coli in all regions. The MICRO grading showed an overall lack of standardization. Conclusion: This review highlights a general increase in AMR reporting and in resistance over time. However, there were substantial problems with diagnostic microbiological data quality. Urgent strengthening of laboratory capacity, standardized testing, and reporting of AST results is required to improve AMR surveillance.